2015
DOI: 10.18061/emr.v10i1-2.4601
|View full text |Cite
|
Sign up to set email alerts
|

Empathy as a Tool for Embodiment Processes in Vocal Performance

Abstract: One way of understanding empathy in music performance is as a process by which singers closely identify with the characters they encounter and portray in opera or art song. As singers embody these characters, they literally give them voice. Music performance humanizes characters as well as performers and audiences through shared empathetic engagement, resulting in the development of knowledge and understanding within and beyond the immediate musical experience. What is the process a singer goes through in empa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Finding the parameters and unifying gestures while incorporating one's personality ultimately shapes the character (Clark, 2002). Additionally, singers are required to empathize with their characters (termed as "empathic embodiment"), which is aided by conceiving mental imagery of the characters' emotional states (Heisel, 2015).…”
Section: Mirror Neuron Networkmentioning
confidence: 99%
“…Finding the parameters and unifying gestures while incorporating one's personality ultimately shapes the character (Clark, 2002). Additionally, singers are required to empathize with their characters (termed as "empathic embodiment"), which is aided by conceiving mental imagery of the characters' emotional states (Heisel, 2015).…”
Section: Mirror Neuron Networkmentioning
confidence: 99%
“…The knowledge that empathy, namely, FS and EC, can be relevant for the perception of emotions, especially for sad songs, is of great importance in a range of contexts, for example, the training of musicians. Heisel (2015) had already suggested that more empathic musicians can convey emotions more clearly and convincingly, which is often of great importance for the success of their performance. The results found here can be interpreted as support for this suggestion, meaning that some facets of empathy may be essential to consider in the apprenticeship of musicians.…”
Section: Prl Genementioning
confidence: 99%
“…We also explored character work from the very beginning, inviting Tyrone, Shawn's alter ego, into the rehearsal space as emotional backup. Heisel (2015) suggested that physicalizing a character can help establish empathy in performance, where "singers who allow natural physical responses to emotions experienced by a character, in the forms of gestures, for example, may find that the doing of these actions leads to deeper empathic engagement with the character" (p. 105). By rehearsing in character, even informally, Shawn was able to deeply connect the experience of singing with the experience of performing; in a way, rehearsal was always the big game, so performance became the championship.…”
Section: Charactermentioning
confidence: 99%